2004
DOI: 10.1111/j.1460-9592.2004.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Safe and effective sedation and analgesia for bone marrow aspiration procedures in children with alfentanil, remifentanil and combinations with midazolam

Abstract: Remifentanil, alfentanil, remifentanil-midazolam, and alfentanil-midazolam combinations are effective in children and can be used safely in bone marrow aspiration which is a brief but painful procedure performed in the pediatric patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 21 publications
(24 reference statements)
2
19
0
2
Order By: Relevance
“…Several studies in pediatric populations have shown that use of intravenous sedation or general anesthesia can improve tolerance of bone marrow aspirates. [23][24][25] However, there are many reasons why sedation and general anesthesia are not used more frequently. Sedation and anesthesia carry small risks of adverse reactions and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in pediatric populations have shown that use of intravenous sedation or general anesthesia can improve tolerance of bone marrow aspirates. [23][24][25] However, there are many reasons why sedation and general anesthesia are not used more frequently. Sedation and anesthesia carry small risks of adverse reactions and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of alfentanil in pediatric procedural sedation has been evaluated by several studies. Antmen et al investigated the efficacy and safety of alfentanil alone, or in association with midazolam, in providing analgo-sedation in children who underwent a diagnostic bone marrow aspiration, stating that both of these schedule are effective [11]. Our results are in keeping with this study, confirming that the use of alfentanil, in association with propofol, is safe and effective for pain relief in children with ALL, even if a particular attention must be taken on its important side effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, when used alone a relatively large dose may be required to provide satisfactory comfort and such high doses may be responsible of cardiovascular and respiratory depression [9,10]. Alfentanil is a synthetic opioid, chemically related to fentanyl, with a rapid onset and short elimination halflife used for short time pediatric painful procedures, such as bone marrow aspiration [11,12]. Ketamine is a shortacting analgesic drug that has been extensively used for pediatric procedures in and out of the operating room and appears to be the preferred agent for parents and physicians.…”
Section: Introductionmentioning
confidence: 99%
“…As previously stated, research regarding the safety and efficacy in NORA has been limited by a lack of large data sets that would be required to detect relatively low frequency occurrences. As we have emphasized in this review, virtually all previous studies that look at the provision of anesthesia or sedation of children outside the OR attempt to assess safety and efficacy despite a cohort that is actually quite small -usually tens or hundreds of patients [11,12]. Again we would note that these studies (which really describe deep sedation/anesthesia) are produced by oncologists, emergency medicine physicians and intensivists, but rarely reported by anesthesiologists.…”
Section: Pediatric Sedation Outcomesmentioning
confidence: 95%